К вопросу о стеклоделии в ранневизантийском Херсонесе - Голофаст, Л.А. (Материалы по археологии, истории и этнографии Таврии, 1998)
Uncovered in the 60s in the XXVth quarter of the Northern district of Cherson site remains of glass-making workshop and several deposits with waste of glassmaking production were traditionally dated by all glass investigators back to the late 4th - mid-5th centuries. But as the result of attentive study of glass and ceramic material of these deposits they split up into two chronological groups: the first, including workshop, was d the late 4th - mid-5th centuries and the second- the late 6th - early 7th centuries. The author has come to the conclusion that on the place of the XXVth and neighbouring XXVIII quarters there was glass-making region functioning from the late 4th till the late 6th centuries when it went to ruin in the result of some catastrophic destruction of the whole town.